Convulsive status epilepticus in children - Alotaibi, Khalid Nijr (2017)
Convulsive status epilepticus (CSE) is an emergency condition associated with mortality and morbidity. It is commonly treated with antiepileptic drugs (AEDs), but these may cause serious adverse events and even death in children. Research on their effectiveness for CSE, and related adverse events in children remains limited. The primary aim of this research was thus to evaluate the effectiveness and safety of AEDs in treating acute tonic-clonic seizure including convulsive status epilepticus (CSE). Two systematic reviews and meta-analyses were conducted to address these aims. The first evaluated the effectiveness of AEDs in children with acute tonic-clonic seizures including (CSE). The second evaluated the safety of AEDs in this population.